If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -21) + (6x + 27) = 90 Reorder the terms: (-21 + 8x) + (6x + 27) = 90 Remove parenthesis around (-21 + 8x) -21 + 8x + (6x + 27) = 90 Reorder the terms: -21 + 8x + (27 + 6x) = 90 Remove parenthesis around (27 + 6x) -21 + 8x + 27 + 6x = 90 Reorder the terms: -21 + 27 + 8x + 6x = 90 Combine like terms: -21 + 27 = 6 6 + 8x + 6x = 90 Combine like terms: 8x + 6x = 14x 6 + 14x = 90 Solving 6 + 14x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 14x = 90 + -6 Combine like terms: 6 + -6 = 0 0 + 14x = 90 + -6 14x = 90 + -6 Combine like terms: 90 + -6 = 84 14x = 84 Divide each side by '14'. x = 6 Simplifying x = 6
| K^2-8k-3=0 | | 21x+42=11-x+2 | | 16x^3y-12x^2y^4= | | a+(-12)= | | (x+2)-(-x-3)=3 | | 21x^12y^12/3x9y^6= | | 36/3/4= | | (2x+15)+(5x-2)=90 | | 8y-40+y= | | -4(3-x)=5(x-2) | | 12x-5=2x-15 | | -2x^2+5x-18= | | 5x-4=3-2(x+4) | | (7x)(3x^4)(x^5)= | | 3-61/2-5-31/4= | | 3-61/2+5-31/4= | | 0.70x+.25(70)=.60(x+70) | | -6k^2-13k-2=0 | | 5/1/2/3=27/x | | (2x-13)+x=122 | | .375=/8 | | (3x^2+4x-12)-(5x^2-x+6)= | | 7x-9=x+5 | | abs(4x+15)=6 | | x/0.28=0.5/0.7 | | 6x+33=4x+45 | | 5x+5(3x-3)=125 | | 10p+3q=60 | | (-4x^2)(3x^4)(-2xy^5)= | | X^2-2m=3 | | -6m=48 | | 8y+4(4y-2)+5=45 |